Elite Football Players from Bosnia and Herzegovina and Kosovo and their Body Composition - Jovan Gardasevic; Dusko Bjelica; Marin Corluka; Ivan Vasiljevic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The aim of this research was to determine the differences among the top football players of the club in Bosnia and Herzegovina, CSC Zrinjski Mostar and the top football players of the club in Kosovo FC Trepca ´89, the champions in their countries, in the morphological characteristics and body composition. A sample of 43 subjects was divided into two sub-samples. The first sub-sample of the subjects consisted of 28 players of CSC Zrinjski Mostar of the average age 24.36±4.14, the champions of the Bosnia and Herzegovina in the season 2016/17, while the other sub-sample consisted of 15 players of FC Trepca ´89 of the average age 21.80±3.57, the champions of the Kosovo Championship in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Morphological characteristics in the body composition were evaluated by a battery of 10 variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold, body mass index, fat percentage and muscle mass. The standard central and dispersion parameters of all variables were calculated. The significance of the differences between the players of the top two football clubs in the morphological characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of the two mentioned clubs don't have statistically significant differences by the variables.